RELEVANT ISSUES CONCERNING THE RELOCATION OF CIVIL PROCEEDINGS UNDER THE NEW CODE OF CIVIL PROCEDURE (NCPC) - Andrei Costin GRIMBERG (Challenges of the Knowledge Society)
The change of the new code of civil procedure and obvious the entry of the new provisions at 15th February 2013, has been thought with the hope to accelerate the procedures related to judgement with a noticeable simplification of procedures, all designed with the aim of unifying the case law and to lower the costs generated by lawsuits , costs both borne by the State as well by citizens involved the cases in court . Thus, the implementation of the New Code of Civil Procedure, desired the compliance right to a fair trial within a optimal time and predictable by the court, by judging the trial in a speedy way , avoiding unjustified delays of the pending cases and to the new petitions introduced, by excessive and unjustified delays often. By the noticeable changes that occurred following the entry into force of the new Code of Civil Procedure, it identify and amend the provisions regarding requests for displacement, in terms of the grounds on which it may formulate the petition of displacement and the court competent to hear such an application.